Fetal surgery for congenital diaphragmatic hernia in Latin America - Cruz-Martínez, Rogelio (2018)
Congenital diaphragmatic hernia is an anomaly in the formation of the diaphragm, which is associated with high neonatal mortality secondary to pulmonary hypoplasia and neonatal pulmonary arterial hypertension. Diagnosis is made by ultrasound, usually in the 20th week of gestation, and it is mandatory to request genetic studies (karyotype and microarrays) due to the high risk of chromosomal and monogenic anomalies. In isolated cases, the estimation of lung size in combination with the identification of liver herniation is the best predictive parameter of neonatal survival. In cases with serious pulmonary hypoplasia, fetoscopic tracheal occlusion has improved the survival rate in 30%. In this article, indications, selection criteria, technique and results of fetoscopic tracheal occlusion are reviewed, and differences in neonatal survival rate in Latin America are highlighted.